A new species of Boulengerula Tornier, 1896 (Amphibia: Gymnophiona: Herpelidae) from Kenya and the “rediscovery” of Boulengerula denhardti - Wilkinson, Mark; Malonza, Patrick K.; Campbell, Patrick; Loader, Simon P. (Zootaxa, 2017)
A new species of herpelid caecilian, Boulengerula spawlsi sp. nov., is described based on nine specimens from Ngaia (= Ngaya or Ngaja) Forest Reserve, Nyambene Hills, Meru County, Kenya collected between 2007 and 2013. The new species differs from all other Boulengerula in having more anteriorly positioned tentacular apertures and tentacular grooves that are partly or completely covered by the maxillopalatines. Specimens of the new species were previously erroneously reported as a rediscovery of the poorly known congener Boulengerula denhardti Neiden, 1912 together with a biogeographic scenario to explain their disjunct distribution that is not required.